2007
DOI: 10.1103/physrevb.76.224109
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature relaxor ferroelectric behavior in Pr-dopedSrTiO3

Abstract: Temperature-dependent Raman scattering, dielectric, and powder x-ray diffraction studies have been carried out on Pr-doped SrTiO 3 ceramic samples. Activation of TO 2 and TO 4 polar modes indicated increasing degree of polar distortion by Pr doping. Dielectric measurements revealed that the system exhibits dielectric relaxation peaks at ϳ500 K. The softening tendency of the polar TO 1 soft mode decreases with increasing Pr doping. X-ray diffraction results show no evidence of symmetry breaking across the diele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
35
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 37 publications
3
35
1
Order By: Relevance
“…In conformity with the previous studies, 15,16 XRPD at 300 K of STP-05 revealed a cubic structure. Figure 1 shows XRPD patterns of the calculated, observed, and difference profiles after Rietveld refinement with the cubic perovskite structure.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…In conformity with the previous studies, 15,16 XRPD at 300 K of STP-05 revealed a cubic structure. Figure 1 shows XRPD patterns of the calculated, observed, and difference profiles after Rietveld refinement with the cubic perovskite structure.…”
supporting
confidence: 92%
“…16 Relative permittivity of platinum electroded ceramic pellet of SPT-05 was measured as a function of temperature with a HP 4192 impedance analyzer. Temperature dependent XRPD study up to 400°C was carried out at HASYLAB ͑B2 beamline͒ at the synchrotron source DESY using a wavelength of 0.79 809 Å ͑calibrated with LaB 6 pattern͒.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is an onset of high temperature dielectric relaxation process beyond 300 K that originates mainly from the presence of polar nano-regions in the sample as already observed from Raman studies. 17 It can be noted that for a given frequency the loss tangent tends to peak ahead of the dielectric constant and the rising (peaking) of both these parameters shifts to higher temperature with increasing frequency, suggestive of features of high temperature relaxor ferroelectricity. …”
Section: Resultsmentioning
confidence: 92%
“…3) where no structural phase transition is expected and is considered as evidence of the existence of polar nano-regions in the material. 17 The smaller effective ionic radii of sixfold coordinated Si 4þ (0.400 Å ) compared with that of Ti 4þ (0.605 Å ) 18 can cause Si 4þ to adopt offcentered positions and create electric dipoles around which polar nano-regions can develop. It was found that the eigenfrequencies of the three TO optical phonon modes (TO 1 TO 2 and TO 4 ) 19 that characterize dielectric response of SSTO are lower (softened) in comparison with that of pure STO.…”
Section: Resultsmentioning
confidence: 99%